2022
DOI: 10.1093/bbb/zbac014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-dose 290 nm UV-B on resveratrol content in grape skins

Abstract: UV-C irradiation increases resveratrol content in grape skins, but it reaches a maximum at a certain UV-C dose. In contrast, UV-B has a weak resveratrol-enhancing effect at low doses, but it has not been investigated at high doses. In this study, we investigated the effect of high-dose UV-B on resveratrol contents in grape skins. Irradiation of Muscat Bailey A with 290 nm UV-B LED at 22 500 and 225 000 μmol m−2 increased the resveratrol contents in the grape skins by 2.1- and 9.0-fold, respectively, without si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The study by Liu et al [217] showed that they have a neuroprotective effect. Resveratrol has also been found in grapes, and its responsibility for the low incidence of coronary heart disease and for preventing amyotrophic lateral sclerosis, cancer growth, and kidney aging [218] has been shown. Various studies have investigated different ways of reusing these benefits, like the creation of coatings with grape seed extract, grape pomace extract, and grape seed oil, the creation of coatings of grape or grape pomace, and the creation of coatings to grape and grape pomace to make infusions.…”
Section: Application Of Edible Coatings For Preparation Of Grapevine ...mentioning
confidence: 99%
“…The study by Liu et al [217] showed that they have a neuroprotective effect. Resveratrol has also been found in grapes, and its responsibility for the low incidence of coronary heart disease and for preventing amyotrophic lateral sclerosis, cancer growth, and kidney aging [218] has been shown. Various studies have investigated different ways of reusing these benefits, like the creation of coatings with grape seed extract, grape pomace extract, and grape seed oil, the creation of coatings of grape or grape pomace, and the creation of coatings to grape and grape pomace to make infusions.…”
Section: Application Of Edible Coatings For Preparation Of Grapevine ...mentioning
confidence: 99%